THE ROLE OF LOCAL INSTITUTIONS IN THE TRANSMISSION OF INFORMATION AND KNOWLEDGE IN INDUSTRIAL DISTRICTS. A SOCIAL NETWORKS ANALYSIS - Luís Martínez-Cháfer; Josep Capó-Vicedo; F. Xavier Molina-Morales (European Regional Science Association (ERSA), 2011)
In recent times, the international competitive panorama has undergone intense rapid change, due especially to the presence of new competitors, new technology and new markets. These changes and their repercussions have had a significant impact on many industrial districts, which has left many of these agglomerations in critical condition. When facing these new circumstances, the function of local institutions takes on a much greater importance in how these districts adapt to the new competitive context, connecting companies with external networks which give access to new sources of information and knowledge. Furthermore, the role of local institutions will always be conditioned by the context in which they are found. For instance, there are significant differences between traditional or low-tech districts and high-tech districts which offer technologically more advanced products and services. Thus, while for the second category there is a great deal of theoretical and academic evidence that supports the idea that institutions act as leader actors in processes of innovation and improvement, in districts which operate in traditional sectors there is a shortage of research that analyzes the role played by institutions in these low-tech districts. To fill this gap in the literature, we aim with this work to analyze the links established by the companies of two industrial districts, with different levels of innovation activity, with local institutions. We especially analyze the intermediary and pollinating function that these institutions can have within these districts. We have applied Social Network Analysis techniques, analyzing the structure and properties of networks in the district as well as the role played by institutions. Our aim is to contribute to the debate by establishing a way to measure the flows of information and knowledge between companies and local institutions in two different districts through a social network analysis. The results obtained are of particular interest and are in contrast with the more traditional view that assumes a positive association between the companies' opportunities for learning and the cohesion of the network.
Keywords: 330